Defective Pollen Wall 2 (DPW2) Encodes an Acyl Transferase Required for Rice Pollen Development. Issue 1 (31st May 2016) - Xu, Dawei; Shi, Jianxin; Rautengarten, Carsten; Yang, Li; Qian, Xiaoling; Uzair, Muhammad; Zhu, Lu; Luo, Qian; An, Gynheung; Waßmann, Fritz; Schreiber, Lukas; Heazlewood, Joshua L.; et al.
Abstract : The cytoplasmic hydroxycinnamoyl-CoA:ω-hydroxy fatty acid transferase DPW2 plays a fundamental role in male reproduction via the biosynthesis of key components of the anther cuticle and pollen wall. Abstract: Aliphatic and aromatic lipids are both essential structural components of the plant cuticle, an important interface between the plant and environment. Although cross links between aromatic and aliphatic or other moieties are known to be associated with the formation of leaf cutin and root and seed suberin, the contribution of aromatic lipids to the biosynthesis of anther cuticles and pollen walls remains elusive. In this study, we characterized the rice ( Oryza sativa ) male sterile mutant, defective pollen wall 2 ( dpw2 ), which showed an abnormal anther cuticle, a defective pollen wall, and complete male sterility. Compared with the wild type, dpw2 anthers have increased amounts of cutin and waxes and decreased levels of lipidic and phenolic compounds. DPW2 encodes a cytoplasmically localized BAHD acyltransferase. In vitro assays demonstrated that recombinant DPW2 specifically transfers hydroxycinnamic acid moieties, using ω-hydroxy fatty acids as acyl acceptors and hydroxycinnamoyl-CoAs as acyl donors. Thus, The cytoplasmic hydroxycinnamoyl-CoA:ω-hydroxy fatty acid transferase DPW2 plays a fundamental role in male reproduction via the biosynthesis of key components of the anther cuticle and pollen wall.